2015
DOI: 10.5194/bg-12-1683-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tidal controls on trace gas dynamics in a seagrass meadow of the Ria Formosa lagoon (southern Portugal)

Abstract: Coastal zones are important source regions for a variety of trace gases including halocarbons and sulphur-bearing species. While salt-marshes, macroalgae and phytoplankton communities have been intensively studied, little is known about trace gas fluxes in seagrass 5 meadows. Here we report results of a newly developed dynamic flux chamber system that can be deployed in intertidal areas over full tidal cycles allowing for high time resolved measurements. The trace gases measured in this study included carbon d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 96 publications
2
34
0
Order By: Relevance
“…Similarly, CH 4 fluxes were more than 4-fold higher in Zostera noltii sediments compared to bare sediments in a temperate intertidal system (12.8 and 3 µmol CH 4 m −2 h −1 , respectively) (Bahlmann et al, 2015), and Alongi et al (2008) reported an increase in CH 4 release associated to an increase in seagrass productivity. Altogether, our findings and consistent literature reports suggest that organic exudates from seagrasses are fueling a complex microbial community including methanogenic Archea.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, CH 4 fluxes were more than 4-fold higher in Zostera noltii sediments compared to bare sediments in a temperate intertidal system (12.8 and 3 µmol CH 4 m −2 h −1 , respectively) (Bahlmann et al, 2015), and Alongi et al (2008) reported an increase in CH 4 release associated to an increase in seagrass productivity. Altogether, our findings and consistent literature reports suggest that organic exudates from seagrasses are fueling a complex microbial community including methanogenic Archea.…”
Section: Discussionmentioning
confidence: 87%
“…Increasing water temperature led to a decrease in the CH 4 / CO 2 ratio. While there was ∼ 7 % of sequestered carbon released as CH 4 to the atmosphere in vegetated sediments at 25 • C (on day two ), it decreased to ∼ 0.8 % in vegetated sediments at 37 • C. In contrast, Banerjee et al (2018) reported ∼ 1 % of carbon being released as CH 4 .…”
Section: Effect Of Warmingmentioning
confidence: 90%
“…and Halophila sp. meadow in India showed a net CO 2 release (dry season: 1190 ± 1600 µmol CO 2 m −2 d −1 ; wet season: 18 400 ± 8800 µmol CO 2 m −2 d −1 ; Banerjee et al, 2018). Both values reported were measured at higher temperatures (dry season: 30±0.68 • C; wet season: 27.94±0.72 • C; Banerjee et al, 2018) compared to our fluxes measured at 25 • C, also indicating that temperature might lead to higher fluxes.…”
Section: Effect Of Warmingmentioning
confidence: 99%
“…Methane (CH 4 ), after CO 2 the most important of greenhouse gases, is to a large degree emitted from wetlands, which can contribute as much as 30%-50% of the global emissions (Bridgham, Cadillo-Quiroz, Keller, & Zhuang, 2013;Laanbroek, 2009;Stocker et al, 2013;Whiting & Chanton, 1993). How seagrass systems might contribute to these emissions has received comparably little attention, although valuable studies have been published (Bahlmann et al, 2015;Barber & Carlson, 1993;Deborde et al, 2010;Garcias-Bonet & Duarte, 2017;Oremland, 1975). Temperature increases have been shown to enhance methane emissions from freshwater systems (Yvon-Durocher, Hulatt, Woodward, & Trimmer, 2017;Yvon-Durocher, Montoya, Woodward, Jones, & Trimmer, 2011), and recently, it has been shown that methane emission from seagrass meadows rises substantially when seagrasses are disturbed (Burkholz, Garcias-Bonet, & Duarte, 2019;Lyimo et al, 2017), and based on calculations of methane emission in seagrass sediments from the Red Sea, it has been suggested that the present estimations of methane emissions from natural systems might have to be increased by about 30% to account for hitherto unrecognized contributions from seagrass systems (Garcias-Bonet & Duarte, 2017).…”
Section: Introductionmentioning
confidence: 99%